Review of the genus Coreodrassus (Araneae: Gnaphosidae) from China - Zhang, Feng; Zhu, Ming-Sheng (Zootaxa, 2008)
The formerly monotypic spider genus Coreodrassus Paik, 1984, belonging to the family Gnaphosidae, is reviewed. A new species, Coreodrassus forficalus sp. nov., is described, and the type species, Coreodrassus lancearius (Simon, 1893) is redescribed.